2020
DOI: 10.1182/blood.2019001262
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of spontaneous CLL regression highlights genetic and microenvironmental interdependency in CLL

Abstract: Spontaneous regression is a recognized phenomenon in chronic lymphocytic leukemia (CLL) but its biological basis remains unknown. We undertook a detailed investigation of the biological and clinical features of 20 spontaneous CLL regression cases incorporating phenotypic, functional, transcriptomic, and genomic studies at sequential time points. All spontaneously regressed tumors were IGHV-mutated with no restricted IGHV usage or B-cell receptor (BCR) stereotypy. They exhibited shortened telomeres similar to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
0
20
1
Order By: Relevance
“…Our patient met the diagnostic IWCLL criteria. Monoclonal cells in CLL affect the phenotype and function of a variety of innate and adaptive immune cells, leading to an infection-prone environment and reduced immune surveillance ( 4 , 13 , 14 ). Studies have found humoral immune failure in CLL, which may be associated with hypogammaglobulinemia and IgG subclass deficiency ( 3 , 15 17 ), as CLL cells impair the immune system ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient met the diagnostic IWCLL criteria. Monoclonal cells in CLL affect the phenotype and function of a variety of innate and adaptive immune cells, leading to an infection-prone environment and reduced immune surveillance ( 4 , 13 , 14 ). Studies have found humoral immune failure in CLL, which may be associated with hypogammaglobulinemia and IgG subclass deficiency ( 3 , 15 17 ), as CLL cells impair the immune system ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between CRS and systemic inflammatory response syndromes such as haemophagocytic lymphohistiocytosis and macrophage activation syndrome are discussed in Box 1 . Although these and other later-onset inflammatory toxicities have been observed independently of CAR T cell specificity, the published data suggest that they occur more frequently with CD22CAR T cells, which were developed to target tumour relapse secondary to CD19 antigen escape 30 32 .…”
Section: Pathophysiology Of Crsmentioning
confidence: 99%
“…Interestingly, patients with spontaneous regression show reduced T-cell exhaustion and increased T-cell proliferation, confirming the important role of the immune system in CLL progression. 91 Moreover, driver mutations are also present in these patients but they always remain stable without subclonal shifts. 91…”
Section: Pathogenic Mechanisms In the Evolution Of The Diseasementioning
confidence: 99%
“…91 Moreover, driver mutations are also present in these patients but they always remain stable without subclonal shifts. 91…”
Section: Pathogenic Mechanisms In the Evolution Of The Diseasementioning
confidence: 99%